The Effect Of PAD, DAU, DAK , And DBH On The Level Of Regional Financial Independence - Rahmat, Marwa Safira; Rahma, Filasti; Saputri, Andriani (International Journal of Multidisciplinary Learners, 2025)
The national strategy based on regional autonomy implements a policy of decentralization, which aims to develop regional economies in an orderly and sustainable manner. This can be clearly seen in the increasing growth of transfer funds from the central government sent to the regions each year. It is expected that the regions will achieve regional economy with the help of decentralization policy. The purpose of this study is to identify variables that affect regional financial independence through revenue sharing funds, general allocation funds, special allocation funds, and local own-source revenues both partially and simultaneously. The sampling method is census sampling. This research is quantitative, using secondary data. The data analysis technique used is multiple linear regression analysis, classical assumption test, and descriptive statistical test. The hypothesis was tested using the simultaneous f test and partial t test with the help of SPSS 29. The results showed that local own-source revenue had a significant positive effect on regional financial independence, while the General Allocation Fund, Special Allocation Fund, and Revenue Sharing Fund had a significant negative effect on the level of regional financial independence. in addition, Local Own-Source Revenue, General Allocation Fund, Special Allocation Fund, and Revenue Sharing Fund simultaneously have a significant effect on the level of regional financial independence.